"[S]ur les ailes de l'imagination". (April 2014) - Stelzig, Eugene
<x xml:space="preserve">Abstract</x> In his Confessions (1782, 1789) Jean‐Jacques Rousseau asserts the central importance of memory in his life, because it is only through memory that he can be fully present to himself. His most complete celebration of the present through the medium of memory is in the Fifth Walk of his Rêveries (1782), where he recollects his short stay on the island of Saint‐Pierre (1765) by way of his ecstatic experience of "le sentiment de l'existence." The unhappy celebrity writer near the end of his life turns to imaginatively enhanced recollections to supplement his actual experiences on the island by way of a Romantic mnemotherapy as a compensatory mode of remembrance. Rousseau's differing autobiographical accounts (in his Confessions and Rêveries) of his time as a happy recluse on the island are a poeticized version of the biographical facts, and it is only in his final and unfinished work that Rousseau realized most fully the therapeutic strategy of a healing recherche du temps perdu in the prose poetry of the Fifth Walk that constitutes a central document of European Romanticism.